Geochemical, zircon U–Pb–Hf, and whole‐rock Sr–Nd isotopic study of Late Jurassic Sanming A‐type granite in the Wuyi area, Fujian province, Southeast China. (1st December 2017) - Zhao, Xilin; Jiang, Yang; Yu, Shengyao; Xing, Guangfu; Yu, Minggang
Abstract : The Sanming pluton is the only Late Jurassic A‐type granitic intrusion in the Wuyi area, west Fujian Province, Southeast China, and its formation has important implications for our understanding of the tectonic evolution of the region. The U–Pb ages of 157 ± 1 Ma and 159 ± 1.1 Ma were obtained for the pluton by zircon LA–ICP–MS analysis, which is interpreted to be the crystallization age of the Sanming pluton (i.e., Late Jurassic). The pluton has the geochemical characteristics of A‐type granite, such as high K2 O+Na2 O contents (average 7.703 wt%), FeOT /(FeOT  + MgO) ratios (average 0.85), and high 10, 000 Ga/Al values and Zr + Nb + Ce + Y (380–446.1 ppm, average 419.2 ppm) contents, but relatively low CaO, Sr, and Eu contents. Zircon saturation temperatures range from 875 °C to 890 °C, also similar to other A‐type granites. The ( 87 Sr/ 86 Sr)i ratios (0.707368–0.71102) and εNd (t) and εHf (t) values (−5.54 to −6.09, and −6.93 to −1.07, respectively), the 2‐stage Nd model ages of 1.50–1.55 Ga, and 2‐stage Hf model ages of 1.25–1.62 Ga, suggest the pluton was derived by extensive fractionation of melts containing both mantle materials and Mesoproterozoic crustal components. The Sanming A‐type granitic pluton is younger than adakitic rocks in the region (162 Ma), suggesting a localized transition from compressional to intraplate extensional tectonics at 162–159 Ma, with mantle‐derived material playing a crucial role in the formation of A‐type granites in the Wuyi Mountain area. This tectonic transition is explained by localized rollback of the subducting Pacific plate.